2015
DOI: 10.1002/jssc.201500623
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 16 polycyclic aromatic hydrocarbons in cigarette smoke condensate using stable isotope dilution liquid chromatography with atmospheric-pressure photoionization tandem mass spectrometry

Abstract: A stable isotope dilution liquid chromatography tandem mass spectrometry method for the analysis of 16 polycyclic aromatic hydrocarbons in cigarette smoke condensate was developed and validated. Compared with previously reported methods, this method has lower limits of detection (0.04-1.35 ng/cig). Additionally, the proposed method saves time, reduces the number of separation steps, and reduces the quantity of solvent needed. The new method was applied to evaluate polycyclic aromatic hydrocarbon content in 213… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The OV7620 is a highly integrated, high-resolution CMOS digital image sensor [19] with an integrated internal light-sensing unit and A/D converter device due to the large amount of image data captured by the OV7620. The standard image data is 7.68 KB per frame and only 37 ns per 1-pixel output.…”
Section: Design Of Acquisition System Under the Fuzzy Quadratic Theorymentioning
confidence: 99%
“…The OV7620 is a highly integrated, high-resolution CMOS digital image sensor [19] with an integrated internal light-sensing unit and A/D converter device due to the large amount of image data captured by the OV7620. The standard image data is 7.68 KB per frame and only 37 ns per 1-pixel output.…”
Section: Design Of Acquisition System Under the Fuzzy Quadratic Theorymentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants formed from incomplete combustion of organic matter ( Stogiannidis and Laane, 2015 ). People can be potentially exposed to PAHs from numerous sources including fuels such as oil, gas, coal, wood ( Hu et al, 2011 ; Choosong et al, 2014 ; Rodrigues et al, 2014 ; Bencsath et al, 2015 ; Negri et al, 2016 ; Roy et al, 2017 ), diet ( Rose et al, 2015 ), and smoking cigarettes ( Li et al, 2008 ; McAdam et al, 2013 ; Slezakova et al, 2014 ; Zhang et al, 2015 ). Some PAHs induce tumors in animals and are carcinogenic to humans ( ATSDR, 1995 ; IARC, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that exposure to PAHs can lead to an increased risk of cancer and as such, PAHs are classified as potential carcinogens [13]. PAHs have been detected in environmental and combustion-related samples such as coal tar [410], diesel particulate matter [11], crude oil [12], air particulate matter [13], mussels [14], sediments [14], and cigarette smoke particulate [15]. The National Institute of Standards and Technology (NIST) has developed a variety of natural matrix Standard Reference Materials (SRMs) for use in validating new and current analytical methodologies for the determination of PAHs [14].…”
Section: Introductionmentioning
confidence: 99%